The evil eye as witchcraft technique in the Hebrew Bible - Kotze, Zak (Journal for semitics, 2007)
The evil eye is a most neglected topic in research on the ancient Israelite language and religion. Despite the ubiquity of this belief in the ancient Near East, some scholars still deny its existence in the Hebrew Bible. This essay attempts to demonstrate that the malevolent eye is attested in the language of the ancient Israelites. A cognitive linguistic analysis of several figurative expressions in the wisdom literature reveals that these were motivated by the conviction that the eye of certain people served as a magical instrument of harm. Especially noteworthy is the fact that the evil eye is ascribed to the black magician.